ADDITIONAL FINANCIAL STATEMENTS PREPARATION FOR THE PURPOSES OF BUSINESS SUCCESS REVIEW OF PUBLIC SECTOR ENTITIES ACCORDING TO IAS FOR THE PUBLIC SECTOR - Borović, Natalija; Zakić, Vladimir (International Journal of Economic Practice and Policy, 2017)
This paper aims to examine the specificity of interpretation of the business success of public sector entities and the implications of this observation on the restriction of information content of the official financial statements. The specificity of the business performance of public sector entities is reflected in the predominantly non-profit character of the realization of business results, as a result of the primacy of meeting the public interest, as the main reason for the functioning of the sector, as a whole. In addition, the ability to exercise the so-called conditional profitability, as an additional segment of success of secondary importance, requires the inclusion of profit and success criteria, as to obtain a comprehensive picture of the realization of business objectives at the entity level. This way of consideration of business performance, which means inclusion, to profit, and non-profit criteria of success and their mutual comparison, ranking and aggregation at the level of unified criteria to achieve business results requires assembling additional financial statements, in accordance with the regulations of IAS for the public sector.
Keywords: IAS for the public sector; principle of conditional profitability; non-profit success; financial statements; public sector